Evaluating the efficacy of bacterial-assisted phytoremediation using maize (Zea mays L.) to uptake heavy metals from fly ash - Samir Gamal Al-Solaimani; Muhammad Abdusalam Al-Khamis; Ali Muhammad Zabraqy; Kamal Ahmed Mohamed Abo-Elyousr; Noor Muhammad; Muchammad Bima Gegana Sakti (Universitas Sebelas Maret, 2025)
The agricultural sector faces dual challenges of declining soil fertility and unsustainable waste accumulation. This study examines the synergistic effects of fly ash (FA) and plant growth-promoting bacteria (PGPB) on the growth and physiological performance of maize (Zea mays L.) under controlled (potted) conditions. FA, a coal combustion by-product rich in essential minerals, was applied at varying doses (1–4 t ha-1) to assess its potential as a soil amendment with a bacterial strain (BSNK7) inoculated to enhance nutrient uptake and mitigate stress. Results showed a significant increase in fresh and dry biomass, leaf area, and chlorophyll content in treated plants. The combined application of 1 t ha-1 FA in conjunction with PGPB significantly increased fresh biomass by 1.57%, dry biomass by 0.94%, leaf area by 2.21%, and higher chlorophyll content compared to control (FA 0 t ha-1 and without bacteria). In contrast, FA 4 t ha-1, when applied without bacterial inoculation, resulted in reduced fresh biomass by 19.94% and dry biomass by 17.39%, respectively, compared to the control (FA 0 t ha-1 and without bacteria) which indicates the creation of toxicity at elevated doses. These findings suggest that the integrated use of low-dose FA and PGPB can sustainably enhance maize growth while minimizing environmental risks. The Application of appropriate doses of FA with PGPB can increase crop productivity and soil health simultaneously. Further field-based studies are recommended to validate scalability, optimize application rates, and assess the long-term impacts on soil health impacts.